Climate Smart Agriculture: More Than Technologies Are Needed to Move Smallholder Farmers Toward Resilient and Sustainable Livelihoods - Sullivan, Amy; Mwamakamba, Sithembile Ndema; Mumba, Aliness; Hachigonta, Sepo; Sibanda, Lindiwe Majele (FANRPAN, 2012)
Climate Smart Agriculture (CSA) is defined as agricultural practices that sustainably increase productivity and system resilience while reducing greenhouse gas emissions1. CSA helps ensure that climate change adaptation and mitigation are directly incorporated into agricultural development planning and investment strategies. Our perspective on CSA is sustainable agriculture, based upon integrated management of water, land and ecosystems at landscape scale.